Neuromarketing and the advances in the consumer behaviour studies: a systematic review of the literature. (2016) - Cruz, Cassiana Maris Lima; Medeiros, Janine Fleith De; Hermes, Lisiane Caroline Rodrigues; Marcon, Arthur; Marcon, Érico
This study aimed to perform a systematic literature review in order to identify the advances in consumer behaviour research using neuromarketing. Therefore, the methodology proposed by Margarey (2001) was used; later the results were analysed using correspondence techniques. Theoretically, by evaluating the articles selected for the development of this study, it may be stated that academic research has made important contributions regarding neuromarketing, mainly researches performed on the fields of neuroscience and psychology. Analysing the selected sample of articles, it was possible to group the main contributions into, fundamentally, three great dimensions: 1) studies that seek to conceptualise neuromarketing, as well as to describe its applications and methodological possibilities in the development of field studies; 2) studies that seek to map the brain regions involved in decision making processes of buyers; 3) studies that map how information is processed by the brain.